2019
DOI: 10.1074/mcp.ra118.001199
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Reveals Multiple Phenotypes Associated with N-linked Glycosylation in Campylobacter jejuni

Abstract: N-linked protein glycosylation (Pgl) in Campylobacter jejuni is required for chicken colonization and human virulence, yet its biological role remains unknown. pgl gene deletion resulted in a significant rearrangement of the C. jejuni proteome that leads to alterations in crucial phenotypes including stress response, nutrient uptake, electron transport and chemotaxis, and is essential for full activity of the Nap nitrate reductase. N-glycosylation therefore contributes to multiple "virulence" phenotypes in C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 69 publications
9
78
0
1
Order By: Relevance
“…We provide evidence that loss of protein glycosylation causes global metabolic defects in B. cenocepacia concerning the utilization of several different carbon sources and tolerance to osmotic and oxidative stress. Therefore, general protein O-glycosylation is required for metabolic fitness, possibly because it is involved in the stability of its protein targets, as shown in C. jejuni (46,47). We also found that not only are glycosylation defective mutants less virulent in the Galleria mellonella infection model, but also that the pathogen-host interaction at the cellular level is different.…”
Section: Discussionmentioning
confidence: 52%
“…We provide evidence that loss of protein glycosylation causes global metabolic defects in B. cenocepacia concerning the utilization of several different carbon sources and tolerance to osmotic and oxidative stress. Therefore, general protein O-glycosylation is required for metabolic fitness, possibly because it is involved in the stability of its protein targets, as shown in C. jejuni (46,47). We also found that not only are glycosylation defective mutants less virulent in the Galleria mellonella infection model, but also that the pathogen-host interaction at the cellular level is different.…”
Section: Discussionmentioning
confidence: 52%
“…This glycan diversity represents a significant challenge to the field as it makes the identification of novel bacterial glycoproteins a non-trivial analytical undertaking. Yet, through advancements in mass spectrometry (MS) [28, 30, 33, 34], these once obscure modifications are increasingly recognisable and are now known to be essential for bacterial fitness [26, 3538]. Despite our ability to generate rich bacterial glycopeptide data the field still largely uses manual interrogation to identify and characterise novel glycosylation systems [2332].…”
Section: Introductionmentioning
confidence: 99%
“…Only recently have mechanistic insights emerged on how the loss of glycosylation affects bacterial physiology and pathogenesis. In Campylobacter jejuni, the loss of glycosylation results in decreased stability of the majority of known glycoproteins, which in turn affects virulence (63,64). These data support a model whereby bacterial N-linked glycosylation contributes to protein stability, but it is unclear whether other glycosylation systems, such as O-linked glycosylation, have evolved to stabilize glycosylated proteins.…”
Section: Introductionmentioning
confidence: 81%
“…Acinetobacter baumannii (55) and C. jejuni (63), but the link of this phenotype to alterations in regulations have not previously documented. Previous studies in B. cenocepacia have identified that not all CepR/I regulated proteins are required for biofilm formation.…”
Section: The Observation That Biofilm Formation Is Reduced In Pgll Mmentioning
confidence: 99%